Sodium/myo-Inositol transporters: substrate transport requirements and regional brain expression in the TgCRND8 mouse model of amyloid pathology. - Daniela Fenili (PLoS ONE, 2011)
Inositol stereoisomers, myo- and scyllo-inositol, are known to enter the brain and are significantly elevated following oral administration. Elevations in brain inositol levels occur across a concentration gradient as a result of active transport from the periphery. There are two sodium/myo-inositol transporters (SMIT1, SMIT2) that may be responsible for regulating brain inositol levels. The goals of this study were to determine the effects of aging and Alzheimer's disease (AD)-like amyloid pathology on transporter expression, to compare regional expression and to analyze substrate requirements of the inositol transporters. QPCR was used to examine expression of the two transporters in the cortex, hippocampus and cerebellum of TgCRND8 mice, a mouse model of amyloid pathology, in comparison to non-transgenic littermates. In addition, we examined the structural features of inositol required for active transport, utilizing a cell-based competitive uptake assay. Disease pathology did not alter transporter expression in the cortex or hippocampus (p>0.005), with only minimal effects of aging observed in the cerebellum (SMIT1: F(2,26) = 12.62; p = 0.0002; SMIT2: F(2,26) = 8.71; p = 0.0015). Overall, brain SMIT1 levels were higher than SMIT2, however, regional differences were observed. For SMIT1, at 4 and 6 months cerebellar SMIT1 levels were significantly higher than cortical and hippocampal levels (p<0.05). For SMIT2, at all three ages both cortical and cerebellar SMIT2 levels were significantly higher than hippocampal levels (p<0.05) and at 4 and 6 months of age, cerebellar SMIT2 levels were also significantly higher than cortical levels (p<0.05). Inositol transporter levels are stably expressed as a function of age, and expression is unaltered with disease pathology in the TgCRND8 mouse. Given the fact that scyllo-inositol is currently in clinical trials for the treatment of AD, the stable expression of inositol transporters regardless of disease pathology is an important finding.